Evaluation Of Cold Chain Practices in Urban Health Centers of a Metro City in India - Lalitha Krishnappa; Arvind B Anniappan; Narayana H Voderhobli; Shantha Kumar Krishna; Sudarshana Yathiraj; Pruthvish Sreekantaiah (Medsci Publications, 2014)
Background: National Family Health Survey report (NFHS)-3 reports revealed that immunization coverage in India among children between 12-23 months was low at 43.5%. In lieu of strengthening Routine Immunization (RI), Government of Karnataka undertook state-wide training of Medical officers and Health workers on RI with concurrent efforts of strengthening cold chain system in health centers. With this background, this study was undertaken to assess the cold chain practices in urban health centers of Bangalore city. Methodology: This Cross-sectional study was conducted during October-December 2008 in three-zones of Bruhat Bangalore Mahanagara Palike (BBMP) covering 35 units. Physical verification of the available cold chain equipments was done using predesigned pretested checklist and face to face interview of cold chain handlers was employed. Results: Of 35 centers, 33(94%) and 32(91%) of them had atleast one functional Ice-lined refrigerator(ILR) and one deep freezer(DF) respectively. Good storage code practice was practiced in 12 out of 33 ILRs. Functional thermometer was available in 31(91%) ILRs of which 23(74%) had temperature in the recommend range. With respect to knowledge of cold chain handlers on RI, 86% were trained on RI and their overall knowledge regarding cold chain practices was satisfactory except for knowledge on temperature in DF and on conditioning of ice-packs. Conclusion: Availability of cold chain equipments has improved and Cold storage practice was good/fair in most of the centers. Knowledge of cold chain handlers was low with respect to select cold chain practices.